2016
DOI: 10.4028/www.scientific.net/kem.688.204
|View full text |Cite
|
Sign up to set email alerts
|

An Environmental Impact of a Wooden and Brick House by the LCA Method

Abstract: The main objective of this paper thesis is to determine the environmental impact of two houses made of two alternative materials - a wooden and a brick house - using a Life Cycle Assessment (LCA). By comparing the material composition of their design to determine the environmental impacts of global warming, human health, consumption of resources and ecosystem quality. An overall comparison showed that the materials for the construction of a wooden house have less negative impact on the environment than materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…They also found that the TPS technique is more universal than the transient hot wire (THW) or the transient hot strip (THS) methods, where the temperature measurement is localized to the thermocouple hot junction. Comparisons with proven older techniques, such as the steadystate and laser flash method, have demonstrated similar results, establishing that the TPS technique offers new opportunities for characterizing the thermal properties of wood, especially in the green state (Dupleix et al 2012;Gaff et al 2016;Kvasnová et al 2016;Mitterpach and Štefko 2016). Li et al (2013) proposed a modified step-wise transient method with special considerations of heat-loss effect occurring at the edge of measured samples, finite geometry of the sample, and orthotropic thermal conductivity.…”
Section: Introductionmentioning
confidence: 74%
“…They also found that the TPS technique is more universal than the transient hot wire (THW) or the transient hot strip (THS) methods, where the temperature measurement is localized to the thermocouple hot junction. Comparisons with proven older techniques, such as the steadystate and laser flash method, have demonstrated similar results, establishing that the TPS technique offers new opportunities for characterizing the thermal properties of wood, especially in the green state (Dupleix et al 2012;Gaff et al 2016;Kvasnová et al 2016;Mitterpach and Štefko 2016). Li et al (2013) proposed a modified step-wise transient method with special considerations of heat-loss effect occurring at the edge of measured samples, finite geometry of the sample, and orthotropic thermal conductivity.…”
Section: Introductionmentioning
confidence: 74%
“…In our study, taking into account only external walls, this difference is 22% for the building with standard insulation. Mitterpach and Štefko [46] found that the materials for the construction of a brick house leave twice the carbon footprint in the environment than materials for a wooden house, but in this case it was a wooden log building.…”
Section: The Influence Of Building Materialsmentioning
confidence: 99%
“…The construction of a sustainable future requires meticulous attention to the materials and practises utilised in the building sector, where both masonry and wood constructions have been widely adopted but are controversial due to their respective impacts on the environment [13][14][15]. This study emerges from a need to comprehend and contrast the carbon footprints of buildings constructed from these materials, located within the context of a holistic Life Cycle Assessment (LCA) integrated with Building Information Modeling (BIM) technology.…”
Section: Introductionmentioning
confidence: 99%